Dental Patient’s Knowledge and Awareness Regarding Effects of Smoking on Oral Health among Smokers and Nonsmokers: A Comparative Study - Puranik, AK; Mishra, Prashant; Kumar, Sandeep; Dhodapkar, SV (Journal of Orofacial Research, 2013)
Aims and objectives: The aim of the present study is to examine the difference in dental patient’s knowledge and awareness regarding effects of smoking on oral health betweensmokers and nonsmokers. Materials and methods: A cross-sectional questionnaire-based survey was carried out among 199 dental patients from Sri Aurobindo Institute of Dental Science, Indore. A self-prepared questionnaire was used to assess the awareness regarding the effects of smoking on oral health. Chi-square test and multiple linear logistic regression model was applied using statistical package for social sciences (SPSS) software. Results: The prevalence of smoking was 22.6%. Fewer smokers and tobacco users than nonusers thought that oral health and smoking are related (28.0 vs 63.3%, p = 0.009). Multiple linear logistic regression was used to assess the association of each variable with awareness, which showed that smokers are less aware of the oral health effects of smoking than the nonsmokers. Conclusion: Smoking and tobacco using subjects are significantly less aware of the oral health effects of smoking as compared to nonsmokers. Comparative studies in other populations may be warranted to ascertain the validity of these results.